ENERGY FLOW OF THE UPWELLING ECOSYSTEM IN SOUTH CENTRAL VIETNAM - Lanh], [Vo Van; An, Nguyen Tac; Son, Vo Duy (Vietnam Journal of Marine Science and Technology, 2009)
This paper reviewed some approaches from studied results of upwelling ecosystem in the South Central Vietnam (Khanh Hoa-Binh Thuan) in periods before 2000 and 2003 - 2005 such as primary production and the mechanism of nutrients supply of upwelling in the coastal waters, ecological conditions in southwestern monsoon and transitional period, energy transfer of phytoplankton. The productive habitat area and total fishery landings were estimated on the basis of these results.